2013
DOI: 10.4187/respcare.02413
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Early Tracheotomy: A Meta-analysis Based on 6 Observational Studies

Abstract: BACKGROUND: Whether early tracheotomy can improve the clinical outcomes of critically ill patients remains controversial. The current study aimed to discuss the potential benefits of early tracheotomy compared to late tracheotomy with meta-analysis of observational studies. METH-ODS: An electronic search (up to February 28, 2013) was conducted by a uniform requirement, and then clinical data satisfying the predefined inclusion criteria were extracted. RESULTS: Data from a total of 2,037 subjects were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
0
18
1
1
Order By: Relevance
“…Tracheostomy is reported to carry significant advantages over prolonged intubation including patient comfort, increased mobility, improved oral hygiene, airway security, easier pulmonary toilet, decreased laryngeal and upper airway damage, decreased need for sedation and other medication, and straightforward nursing care . Earlier ventilator weaning, decreased length of intensive care unit (ICU) stay, and decreased likelihood of ventilator‐associated pneumonia due to improved pulmonary toilet have also been reported . Although tracheostomy placement is noted to hold these clinically significant advantages; the ideal placement time remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tracheostomy is reported to carry significant advantages over prolonged intubation including patient comfort, increased mobility, improved oral hygiene, airway security, easier pulmonary toilet, decreased laryngeal and upper airway damage, decreased need for sedation and other medication, and straightforward nursing care . Earlier ventilator weaning, decreased length of intensive care unit (ICU) stay, and decreased likelihood of ventilator‐associated pneumonia due to improved pulmonary toilet have also been reported . Although tracheostomy placement is noted to hold these clinically significant advantages; the ideal placement time remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…To address issues of sample size, regional variation, and varying results, several meta‐analyses have been performed. Earlier meta‐analyses suggested insufficient evidence to draw conclusions about timing of tracheotomy . More recently, Griffiths et al in 2005 performed a systematic review and meta‐analysis that ultimately analyzed five randomized or quasirandomized studies, with a total of 406 participants who were assigned to early (up to 7 days) versus late tracheostomy (any time thereafter) with a primary outcome measure of mortality in the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of RESPIRATORY CARE, 2 papers concern tracheotomy in the ICU. The first is from Shan and colleagues, 6 in China, who conclude that early tracheotomy, between the third and seventh day after intubation, decreases mortality, reduces recovery time in the ICU, and shortens mechanical ventilation time in ICU patients. Shan et al conducted a meta-analysis of 6 retrospective series encompassing 2,037 patients.…”
mentioning
confidence: 99%
“…Most of the meta-analyses that embraced prospective studies dealing with our study topic, have suggested that early tracheotomy does not significantly reduce mortality rates 3,5,22,23 . In contrast, one recent meta-analysis found lower overall mortality rates in early tracheotomized patients, but the analysis in question included observational studies only 24 . In accordance with our results, almost all recent prospective randomized studies indicated that early tracheotomy did not influence mortality rates 2,10,[14][15][16][17]20,25 .…”
Section: Discussionmentioning
confidence: 93%